Modern South Korean air power Republic of Korea Air Force today - Polderman, Robin (Harpia Publishing, 2021)
Since the early 1950s, the heavily industrialised nation of South Korea has seen steady growth and is now the world's seventh-largest exporter and 11th-largest economy overall. As the Cold War on the Korean peninsula gathered momentum, the development of the Republic of Korea Air Force became one of the nation's top priorities. While initially dependent on the United States for its aircraft, Korea's aviation industry has matured rapidly, and the ROKAF's use of indigenously manufactured equipment is on the rise. Modern South Korean Air Power provides a detailed look at the aircraft and armament, as well as the organisation and the modernisation process of the ROKAF.